PENGARUH MODEL PENCAPAIAN KONSEP PADA MATERI LOGIKA DASAR TERHADAP HASIL BELAJAR MAHASISWA DI STKIP MUHAMMADIYAH PAGARALAM - Hariani Juwita; Neni Lismareni (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The purpose of this research is to find out the effect of the concept achievement model on basic logic material on student learning outcomes, because this basic logic material is a course in STKIP Muhammadiyah Pagaralam. Model Achievement The concept taken is one of the learning models that invites students to understand the concepts of mathematics learning. The population and sample in this study were STKIP Muhammadiyah Pagaralam students majoring in Semester 1 Mathematics Education. The research method used in this study was the experimental method with the True Experimental Design model in the